Model Kolaborasi Guru PIAUD dan Guru PAI dalam Pengembangan Pembiasaan Ibadah Anak Usia Dini - Polem, Mirwansyah; Ridha, Nikmatur (Prodi PIAUD STAI Sumatera Medan, 2025)
This study aims to analyze the collaboration model between Early Childhood Islamic Education (PIAUD) teachers and Islamic Religious Education (PAI) teachers in fostering worship habits among young children at RA Islamic Center. Using a qualitative phenomenological approach, this research explores teachers’ experiences in designing, implementing, and interpreting collaboration within routine worship activities such as dhuha prayer, daily supplications, wudu practice, and the introduction of hijaiyah letters. The informants consisted of four PIAUD teachers, two PAI teachers, and one school principal selected through purposive sampling. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed through data reduction and thematic development. The findings show that collaboration is formed through intensive communication and complementary competencies between the two groups of teachers. PIAUD teachers contribute by adapting methods according to children's developmental stages, while PAI teachers ensure the accuracy of religious content. This synergy produces more meaningful worship habituation through direct experience, role modeling, and enjoyable repetition. The study also reveals that collaboration carries emotional and spiritual meaning for teachers as it becomes a space for mutual learning and strengthening of religious values. The novelty of this research lies in the finding that collaboration is not merely technical but also shapes a shared interpretive process that enriches teachers’ understanding of worship habituation in early childhood.